The size of terroir: A theoretical on economics and politics of geographical indications - Deconinck, Koen; Swinnen, Johan (John Wiley & Sons, 2021)
Geographical indications (GI) certify the geographical origins of a product and delineate the specific area in which the certified product must be produced. Despite a large literature on the economics of GIs, few papers have explored the question of the optimal size of GI regions. This note presents a flexible conceptual framework to explore the economics and politics of the delimitation of a GI. The general framework describes the efficiency and distributional effects of the size of a GI and shows how this affects interest groups’ incentives to influence government decision‐making.